Nonlinear Transport: in Hamiltonian Pump-Ratchet Hybrids (2019)
The pumps and ratchets are benchmark prototypes of systems that generate directed trans- port. In this work we introduce a possible hybrid between these systems, using a model in a Hamiltonian fashion, that combines a spatially periodic static potential with a local driving, with different possibilities of space inversion and time reversal symmetry breaking. In this way, we found manifestations of irregular scattering that leads to net current generation for three types of general models of punchets found, in terms of the way they break the symmetries. Also, is showed how this currents depends on the symmetry manipulation parameters of the model. Further, an approximation to the quantum version of punchets shows discrete energy shifts induced by the periodic time-dependence of the driving as long as asymptotic Bloch states scatters.